The Impact of The Gradual Activities Strategy on The Achievement of The Students of The Department of Art Education In The Subject of Aesthetics (Journal of the College of Basic Education, 2026)
The researcher dealt with the impact of the gradual activities strategy on the achievement of the students of the Department of Art Education in the subject of aesthetics, and the goal was achieved (by rejecting the null hypothesis, which states that there are significant differences between the average achievement of the students of the experimental group who studied aesthetics according to the strategy of graduated activities and the control group that studies the same subject in the same way normal) and the alternative hypothesis is accepted.The researcher used one measuring tool (the achievement test) before and after to calculate the impact of the independent variable (gradual activities strategy) on the dependent variable (achievement) in favor of the experimental group. Technical / College of Basic Education / Al-Mustansiriya University, third stage, numbering 210 students..